Does Employer Branding have a Positive Impact on the Business in midsize and large corporations? - Bose, Aratrika; Legnerová, Kateřina, 1965-; Černá, Daniela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This paper explores the impact of Employer Branding on large corporations, aiming to establish a direct connection with three business performance parameters: overall sales performance, profitability, and market capitalization. Examining seven major organizations, the research focuses on Employer Branding practices such as Employee Value Proposition (EVP), Employee Experience, Employer Reputation, Work-Life Balance, and Employee Engagement. The results reveal a strong correlation between organizational performance and Employer Branding practices, with Microsoft earning the highest score (45) and Amazon the lowest (39) out of 50. The Benchmark 7 organizations exhibited strong business performance; business momentum (even during the COVID 19 pandemic); profitability; market capitalization; resilience; reputation; innovation; speedy response to business interruptions; and others. Future research on this subject can focus on a 'cause and effect' study about which Employer Branding practices impact which brand performance outcome. The research can also eventually try and develop a correlation model which can serve as a guide for brands.
Vedoucí práce: Kateřina Legnerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses